The effect of temperature change on fluoride uptake from a mouthrinse by enamel specimens - Baglar, Serdar; Nalcaci, Adil; Tastekin, Mustafa (European Journal of Dentistry, 2012)
Objective: The aim of this study was to examine the effect of temperature on fluoride uptake by enamel specimens from a 0.05% NaF-fluoridated mouthrinse (Oral-B Advantage; Oral-B Laboratories, Newbridge, UK).Methods: Enamel specimens were prepared from extracted human maxillary central incisors. A fluoride-specific ion electrode was used to measure the uptake from a 2 ppm fluoride solution containing 50.0 mL of distilled water, total ion strength adjustment buffer, and fluoridated rinse at 3 different temperatures (room temperature, 25°C; human body temperature, 37°C; hyper-fever temperature, 43°C). One-way analysis of variance and least significant difference were used to assess intragroup and intergroup differences (P<.05).Results: The study found that both the amount and the rate of fluoride uptake increased significantly with increase in temperature. This effect was particularly noticeable at 43°C.Conclusions: The temperature of the NaF mouthrinse may easily and safely be increased beyond room temperature by placing a container of the NaF mouthrinse in a bowl of hot water, allowing greater fluoride penetration into the enamel from the mouthrinse when used at home as a routine prophylactic agent. (Eur J Dent 2012;6:361-369)
Keywords: Fluoride uptake; temperature; enamel; mouthrinse